Empowering Women to Recognize Maternal Warning Signs. Issue 6 (November 2020) - Killion, Molly M.
Abstract : In May 2020, the Council on Patient Safety in Women's Health Care released an Urgent Maternal Warning Signs program to help pregnant women and women during postpartum recognize active or impending adverse effects requiring medical attention. Our maternity nursing expert, Molly Killion, presents an overview.